Development of an off-the-shelf biomimetic vascular graft for small diameter vascular regeneration - Federici, Angelica Silvia (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2023)
Cardiovascular disease is one of the leading causes of death worldwide. The impairment of blood flow can require a total vessel substitution, but current grafts fail to recapitulate the unique mechanical behavior of native vessels, especially in the case of small diameter vessels (<6mm). Despite the field of tissue engineered vascular grafts (TEVG) demonstrating promising progress, a solution remains elusive, due in part to the lack of compliance match. In this study, melt-electrowriting (MEW) was adopted in combination with other fabrication methods in a strategy to develop a bio-inspired graft, which replicates the unique collagen architecture of the native vessel. Scaffold architectures resembling the ECM organization of the vessel wall successfully matched the mechanical behavior of native vessels, and interestingly acted as a guide to direct cell alignment and preferential ECM deposition. The developed vascular graft satisfied the ISO 7198 requirements and reduced the number of adherent platelets. The proposed off-the-shelf vascular graft proved patency in a rat abdominal substitution model with limited blood cell infiltration. Thus, the tubular graft here designed and developed holds great promise as a TEVG for small diameter applications.
APPROVED
Keywords: Tissue Engineer; Vascular Regeneration; Small Diameter Vascular Graft; Advance Manufacturing; Melt-electrowriting